PENGEMBANGAN MEDIA PEMBELAJARAN POS JUMLAH PADA MATERI PENJUMLAHAN UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA KELAS I SD - Jannah, Hidayatul; Ahmad Hariandi; Akhmad Faisal Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a learning media called Pos Jumlah for addition materials and to examine its validity and practicality. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included first-grade students of SDN 076/I Sungai Buluh, a firstgrade teacher, and material and media experts as validators. Data were collected through expert validation sheets, teacher and student response questionnaires, and numeracy tests in the form of pretests and posttests.The validation results showed that the Pos Jumlah learning media achieved an average score of 91%, categorized as very valid. The results of small-group and large-group trials indicated a very high level of practicality, as reflected by positive responses from both teachers and students, with percentages of 91% and 89%, respectively. These findings indicate that the media is easy to use, engaging, and able to increase student participation during the learning process.Based on the results, it can be concluded that the Pos Jumlah learning media is feasible to be used as an alternative instructional medium in mathematics learning, particularly for addition material in first-grade elementary school. This media is expected to help students understand addition concepts concretely and meaningfully, as well as improve their numeracy skills.